PENGARUH LEVERAGE, LIKUIDITAS, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Arfin Taniman, Jonnardi (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
This study aims to analyze the relationship among proportion of leverage, likuidity, and firm size toward firm value. This research used purposive sampling method. The type data is panel data during 2014-2018 in the from Indonesia Stock Exchange with total sampel was 225 data. Data analysis technique using multiple linear regression with Eviews program 10.0. The results shows that proportion of likuidity have no significant effects on firm value, meanwhile leverage and firm size has significant on firm value.